Laruelle and Non-Philosophy - Mullarkey, John; Smith, Anthony Paul (Edinburgh Edinburgh University Press, 2012)
The first collection of critical essays on the work of this most original thinkers François Laruelle is one of the most important French philosophers of the last 20 years, and as his texts have become available in English there has been a rising tide of interest in his work, particularly on the concept of 'Non-Philosophy'. Non-philosophy radically rethinks many of the most cutting-edge concepts such as immanence, pluralism, resistance, science, democracy, decisionism, Marxism, theology and materialism. It also expands our view of what counts as philosophical thought, through art, science and politics, and beyond to fields as varied as film, animality and material objects.o Provides an overview of Laruelle's thought and an understanding of his contemporary relevanceo Contains an exclusive interview with Laruelle and a new essay written by Laruelle himselfo Includes an annotated bibliography of Laruelle's work and secondary sources
Keywords: Laruelle, François; 20th Century (1901-2000); Philosophy; France